2021
DOI: 10.20944/preprints202112.0117.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Post-editese in Literary Translations

Abstract: In the present study, we investigate the post-editese phenomenon, i.e., the unique features that set machine translated post-edited texts apart from human-translated texts. We use two literary texts, namely, the English children's novel by Lewis Carroll Alice’s Adventures in Wonderland (AW) and Paula Hawkins' popular book The Girl on the Train (TGOTT) translated from English into Brazilian-Portuguese to investigate whether the post-editese features can be found on the surface of the post-edited (PE) … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Several researchers have reported the existence of features of post-edited machine translation output (MTPE) that distinguish it from human translated text (HT), defined as post-editese. By way of example, Castilho et al looked at literary texts Google-translated from English into Brazilian Portuguese and found evidence for post-editese in one of the two texts examined [1]; Volkart et al found that post-edited machine translation was not only lexically poorer than human translation, but also less dense and less varied in terms of translation solutions [12]; Toral found that MTPE was simpler and more normalized and had a higher degree of interference from the source language than HT [11]; and Castilho et al found evidence of post-editese features, especially in light post-edited texts and in certain domains [2]. By contrast, on the other hand, Daems et al found no proof of the existence of post-editese, either perceived or measurable [5].…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have reported the existence of features of post-edited machine translation output (MTPE) that distinguish it from human translated text (HT), defined as post-editese. By way of example, Castilho et al looked at literary texts Google-translated from English into Brazilian Portuguese and found evidence for post-editese in one of the two texts examined [1]; Volkart et al found that post-edited machine translation was not only lexically poorer than human translation, but also less dense and less varied in terms of translation solutions [12]; Toral found that MTPE was simpler and more normalized and had a higher degree of interference from the source language than HT [11]; and Castilho et al found evidence of post-editese features, especially in light post-edited texts and in certain domains [2]. By contrast, on the other hand, Daems et al found no proof of the existence of post-editese, either perceived or measurable [5].…”
Section: Introductionmentioning
confidence: 99%